Dando com a língua no passado: o ser e não ser marcado em discursos, imagens, objetos e paisagens - Juliana de Souza Cardoso (2008)
This is a multidisciplinary study examining the processes of ethnic identity experienced by the Pataxo, an indigenous population that migrated in the 1980s to the Indigenous Reserve Fazenda Guarani in Camesia, Minas Gerais. The themes that guide the research were language, identity, and culture and how they played out in terms ofsubjectivities, adaptation, and survival strategies. The data was analysed using an interactive approach among areas of Linguistics (Discourse Analysis and Anthropological Linguistics), Ecology (Human Ecology and Historical Ecology), and Archeology. In order to uncover the processes of identity building of the Pataxo, I used linguistic and cultural markers found in their discourses, historical and material cultural evidence. Theintegrative analysis of the data revealed a group undergoing processes of restructuration and adaptation with regards to their ethnic identity. This identity proves to be the result of continued efforts by the Pataxo to preserve what they can from their ancestors, while at the same time adjusting to changes taking place in the national society, their representation of indigenous people and their relationship with to natural resources. I have referred to these efforts as survival strategies. A set of linguistic and cultural markers provide the distinctiveness of this group in relation to other groups.